Selecting the Methodological Path: A Beginner’s Guide to Grounded Theory Approaches - Garlan, Michael (Journal of Interdisciplinary Perspectives, 2024)
A grounded theory methodology is a qualitative approach to exploring and describing social processes based on the people's perspective and the researcher's philosophical position. Since the methodological approach is a consequence of the philosophical orientation of the researcher, it is imperative to consider the role of the researcher in the interpretation of the data, the place of the literature review in shaping the theoretical models, the research questions, and the approaches to the data analysis to be able to justify the choice of a specific type of grounded theory approach. Since the grounded theory is too broad a methodology, this article will help provide a novice-level researcher with structuring and developing a grounded theory methodology consistent with the essential elements of each grounded theory type.